Kappa-opioid receptor agonist U50448H protects against renal ischemia-reperfusion injury in rats via activating the PI3K/Akt signaling pathway - Liu, Li-jie; Yu, Jian-jun; Xu, Xiao-lin (Acta pharmacologica Sinica, 2018)
Renal ischemia-reperfusion injury （IRI） is regarded as a leading cause of acute kidney failure and renal dysfunction. Previous studies show that kappa opioid receptor （KOR） agonists can attenuate IRI in cardiomycytes and neuronal cells. In this study we explored the effects of a KOR agonist on renal IRI and the underlying mechanisms in vivo and in vitro. An IRI model was established in SD rats, which were intravenously pretreated with a KOR agonist U50448H （1 mg/kg）, a KOR antagonist Nor-BNI （2 mg/kg） followed by U50448H （1 mg/kg）, or the PI3K inhibitor wortmannin （1.4 mg/kg） followed by U50448H （1 mg/kg）. U50448H pretreatment significantly decreased the serum levels of creatinine （Cr） and BUN, the renal tubular injury scores and the apoptotic index （AI） in IRI model rats. Furthermore, U50448H significantly increased SOD activity and NO levels, and reduced the MDA levels in the kidney tissues of IRI model rats. Moreover, U50448H significantly increased the phosphorylation of Akt, eNOS and PI3K in the kidney tissues of IRI model rats. All the beneficial effects of U50448H were blocked by Nor-BNI or wortmannin pre-administered. Similar results were observed in vitro in renal tubular epithelial NRK-52E cells subjected to a hypoxia-reoxygenation U50448H protects against renal IR} via activating the PI3K/Akt signal （HR） procedure. Our results demonstrate that the KOR agonist ng pathway.